Setbacks of University Teaching in Health Sciences - Hedioneia Maria Foletto Pivetta; Neosane Schlemmer; Patrícia Oliveira Roveda; Silvia Maria de Aguiar Isaia; Sinara Porolnik; Vanessa Michelon Cocco (Universidade Federal do Rio Grande do Sul, 2019)
This article has discussed aspects of the university teaching, found by professors from the health field. This is a qualitative study, with narrative interviews, interpreted by content analysis. Professors' setbacks from distinct courses have been organized into two categories: human and structural dimension. Facing the reality of scrapping of many public higher education institutions (IES), the major difficulties were not related to the infrastructure, but rather the ones involving personal relations, in particular, the multiprofessionality, an aspect considered as very important in the health field training because it allows a comprehensive assistance.